Hegemonic practices of online local fashion brands in the information society era during the Covid-19 pandemic - Wifkil Mu'tamiroh; Bagong Suyanto (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
The Covid-19 pandemic has had an impact on people around the world, including in Indonesia, particularly regarding the social and economic aspects of life, including the online economic agents. This study looks at and analyzes the hegemonic practices carried out by online economic agents in relation to the consumer so then they can survive and benefit during the Covid-19 pandemic. The theory used is hegemony according to Antonio Gramsci. This study used a qualitative research design. The research subjects were the owners of online local fashion brands that have developed in East Java. The primary data was collected from interviews and secondary data is from books and journal articles. The results of this study show that the local brands had a good level of performance during the Covid-19 pandemic, as seen from the observations conducted on Instagram. Hegemonic practices by online economic agents consist of three methods. First, there is using the social media platform Instagram. Second, there is always being productive. Third, there is collaborating with social media influencers (endorsement). The hegemonic practices happened by the social media so that it can influence people to follow their Instagram accounts and buy the products offered.